A Dispositional Theory of Practical Basing - (:unkn) unknown (My University, 2023)
The practical basing relation is the relation that holds between an agent’s action and the reason on the basis of which the agent performs the action. In this thesis, I offer a theory of the practical basing relation called “double dispositionalism” (DD). In a nutshell, I argue that acting on the basis of a reason is doing what one is disposed to consider appropriate. More specifically, I argue that an agent does an action φ on the basis of a reason R if and only if the agent’s φ’ing manifests a reasons-sensitive disposition to φ given R, and the agent has a second disposition to take R to support φ’ing. I defend DD on the following grounds: DD can address the problem of deviant explanatory chains, it does not over intellectualize practical basing, and can explain why acting on the basis of a reason is subject to a tricky form of higher-order defeat (what I call “proper basing defeat”).
Keywords: Dispositions; Higher-Order Defeat; Rationality; The Basing Relation